Pelatihan Membatik Jumputan Sebagai Sarana Menumbuhkan Kreativitas Siswa Kelas V - Faznuhal; Futhoirotul Ufaiwiyah; Fauzan Mirza AM; Fitri Khairani; Abdul Karim; Dewi Yulianawati; Nurlidah (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2024)
This training was aimed at fostering students’ creativity through a tie-dye batik workshop for fifth-grade students at SDN 1 Pasalakan. The program was implemented in three stages: (1) preparation, (2) implementation, and (3) evaluation. The preparation stage involved observing students’ creative activities at school, planning the training program, forming a committee, and drafting a budget plan. The observation showed that SDN 1 Pasalakan had never previously conducted batik training. The activity was organized by the Pre-service Teacher Professional Education (PPG) students, Cohort 2 of 2024, Universitas Muhammadiyah Cirebon. The training was successfully carried out and produced several tie-dye batik fabrics with various patterns that reflected students’ creativity. The recommendation for SDN 1 Pasalakan is to design follow-up programs to further develop students’ creativity, such as workshops on handicrafts made from plastic waste. Practical activities of this kind can engage students physically and mentally, thereby supporting creativity and nurturing love for national culture as reflected in the Pancasila Student Profile.